A Brief Review on Haematoxylin: An Irreplaceable Tissue Stain - Niva Mahapatra1 , N.Aravindha Babu2 , Shyam Sundar Behura3 , E.Rajesh4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Haematoxylin is the most popular nuclear counterstain used in routine histopathogical techniques forstaining tissues. It is derived from the tree Haematoxylum Campechianum (H.campechianum). The historyof haematoxylin reveals centuries of war, strife and discovery dating from the Mayans and Aztecs whoused it as an ink and fabric dye to the war resulting in the invasion of Mexico by European countries.H.campechianum was later named as logwood and block wood by the invaders that used it to generatehaematoxylin crystals to be utilized in textile industry. The recognition to introduce haematoxylin asbiological stain goes to Waldeyer. But later Bohmer introduced the technique of coupling a mordant to thedye making it colorfast and thus, haematoxylin remains a very unique and vital stain in histology till date.